Bibliometric analysis of photocatalytic oxidation of volatile organic compounds from 1998 to 2023 - Zhu, Xinjie; Sui, Yifan; Li, Xiuli; Guan, Jie; Zhang, Xiaojiao; Zhang, Gangfeng; Guo, Yaoguang (Frontiers in Environmental Science, 2024)
Volatile organic compounds (VOCs) have attracted widespread attention due to their adverse effects on human health. Photocatalytic oxidation is an effective technology for degrading VOCs under ambient conditions. In order to better understand the trends and development of global trends in photocatalytic oxidation of VOCs, the analysis of 2493 articles or reviews from the Science Citation Index Expanded (SCIE) in the Web of Science Core Collection, covering the period from 1998 to 2023, was conducted using CiteSpace and VOSviewer software. The findings indicate significant growth in papers concerning photocatalytic oxidation of VOCs. China emerges as the most active country among the main drivers. Principal sources publishing relevant research are Applied Catalysis B-Environmental, Chemical Engineering Journal, Journal of Hazardous Materials, and Environmental Science & Technology. A relatively well-established theoretical framework has been developed for the study of photocatalytic oxidation of VOCs. In the field ofVOCs photocatalytic oxidation, the focus is on the development and optimization of advanced photocatalysts with efficient charge separation, better adsorption performance, and a wider light response range. In addition, the in-depth study of the charge generation and transfer mechanisms within the photocatalysts, as well as the comprehensive understanding of the reaction kinetics and catalytic oxidation process, the optimization of the reaction conditions, and the improvement of the catalytic efficiency are at the forefront of the research in this field. This research system is advancing and becoming more refined, with its theoretical propositions, research findings, and methodologies increasingly employed and confirmed.